Innovative efforts of SMEs: exploring the barriers to successful implementation. Issue 6 (1st January 2012) - Nikolaidis, Yiannis; Bakouros, Ioannis; Skalkos, Dimitris
Innovation is the key aspect through which small and medium sized enterprises can survive during the current global crisis. The paper examines the companies' innovation efforts in a region where the innovation outcome is at a very low level, in order to determine the barriers to innovation, recognise the prospects, the strengths and the weaknesses, and evaluate the influence of the selected parameters. The research is based on data collected through telephone interviews with owners and managers of companies at the North Aegean islanding region of Greece. The study proves that successful innovation is the result of multiple, interconnected factors, which should be developed in parallel in order to ensure positive, sustainable outcome. Thus, areas of innovative improvement can be used as guidelines for the public and private sector of the less developed regions in order to take actions which will strengthen production, and export capacity of the companies.